Anatomical Variations of the Biceps Brachii Muscle in the Nepalese Population: a Cadaveric Study - Jha, Anuja; Chalise, Usha; Lama, Chhiring Palmu; Dhungel, Aryan (Nepal Medical College Journal, 2025)
The biceps brachii is the primary muscle in the anterior compartment of the arm, typically consists of two heads: the long head and the short head. It often presents with anatomical variations, including additional heads, differences in its insertion and nerve supply. The present study aimed to assess these variations in the Nepali population, with a focus on additional heads, insertional variations and nerve connections. The study was conducted on 40 dissected upper limbs from 20 cadavers (18 male and 2 female) in the Department of Human Anatomy at Nepal Medical College Teaching Hospital, Attarkhel, Gokarneshwor-8, Kathmandu, Nepal, from November 2024 to April 2025. The present study observed anatomical variations in 12.5% of the cases, specifically additional heads of the biceps brachii. One rare bilateral variation (2.5%) displayed four heads on one side and three on the other. The four-headed variant included two additional heads originating from the pectoralis major muscle, while the three-headed variant was of the inferomedial humeral type. The inferomedial humeral variation was the most common, found in 10.0% of limbs, with three occurring on the right side. These findings emphasize the inferomedial humeral variation as the most prevalent biceps brachii anomaly. In conclusion, this study revealed additional heads and a communicating branch between the musculocutaneous and median nerves. These anatomical variations can affect function, complicate diagnosis and provide options for reconstructive surgery.